Long-term survival correlates with immunological responses in renal cell carcinoma patients treated with mRNA-based immunotherapy. (3rd May 2016) - Rittig, Susanne M.; Haentschel, Maik; Weimer, Katrin J.; Heine, Annkristin; Müller, Martin R.; Brugger, Wolfram; Horger, Marius S.; Maksimovic, Olga; Stenzl, Arnulf; Hoerr, Ingmar; Rammensee, Hans-Georg; Holderried, Tobias A.; et al.
ABSTRACT: Renal cell carcinoma (RCC) is an immunogenic tumor for which immunotherapeutic approaches could be associated with clinically relevant responses. It was recently shown, that induction of T-cell responses against multiple tumor-associated antigen (TAA) epitopes results in prolonged overall survival in RCC patients. In 2003–2005, we performed a phase I/II trial testing an mRNA-based vaccine formulation consisting of a mixture of in vitro transcribed RNA coding for six different TAAs (MUC1, CEA, Her2/neu, telomerase, survivin, MAGE-A1) in 30 metastatic RCC (mRCC) patients. In the first 14 patients, vaccinations were applied i.d. on days 0, 14, 28, and 42. In the consecutive 16 patients, an intensified protocol consisting of i.d. injections (daily on days 0–3, 7–10, 28, and 42) was used. After the respective induction periods, patients in both cohorts were vaccinated monthly until tumor progression. At survival update performed in July 2015, one of the 30 patients was still alive. One patient was lost to follow-up. Median survival of 24.5 mo (all patients) and 89 mo (favorable risk patients) exceeded predicted survival according to Memorial Sloan Kettering Cancer Center (MSKCC) risk score. Impressively, long-term survivors displayed immunological responses to the applied antigens while vice versa no patient without detectable immune response had survived more than 33 mo. The current survival update shows a clear correlation between survival and immunological responses to TAAs encoded by the naked mRNA vaccine. This is one of the first vaccination studies and the only RNA trial that reports on safety and efficacy after a follow-up of more than 10 y.